Conditional secondary transfer effect: The moderating role of moral credentials and prejudice. (October 2021) - Jasinskaja-Lahti, Inga; Vezzali, Loris; Ranta, Mona; Pacilli, Maria Giuseppina; Giacomantonio, Mauro; Pagliaro, Stefano
This survey experiment examined the role of prejudice and moral licensing as two moderators of the secondary transfer effect (STE) of positive and negative intergroup contact. We collected a quota-randomized sample of 299 majority Finns (52.6% female; experimental condition: n = 118, control condition: n = 181) in order to test whether moral credentials prevent attitude generalization (from primary towards secondary outgroup), particularly among prejudiced individuals. The results showed that STEs of both positive and negative contact were prevented among more prejudiced majority group members who had the possibility to obtain moral credentials in the moral licensing task. These results point at the unstable nature of attitude generalization in STE among prejudiced individuals and at the potential of a normative moral act to intervene into the generalization of intergroup attitudes following intergroup contact. We discuss these findings in relation to the literature on moral licensing and moral reinforcement, framing them in the context of an integration of contact research and research on morality in general.